La auditoría interna y su incidencia en las operaciones financieras y administrativas de la COAC “KULLKI WASI”, período 2018-2019 - Nelson Fabian, Mungabusi Galarza (2021)
ABSTRACT Internal auditing provides management with the necessary tools to achieve operational efficiency by identifying problems and correcting them. This research aims to know the contribution provided by the internal auditor to the financial and administrative operations at Coac Kullki Wasi Ltda by verifying whether the auditor provides support and advice CEO's, managers, and employees of the credit union require. The method applied to this research was the deductive method, the type of research was documentary because it was necessary to manipulate information provided by the company. This research was a field study because we went to Coac Kullki Wasi facilities. The bibliographic approach was also used because it functioned as theoretical support for the study. The research was non-experimental, having a quantitative and qualitative approach that helped data collection. The analysis was descriptive because it describes how the internal auditor contributes to the financial and administrative operations of the company. The population with which the research was carried out consisted of eleven people comprising the department heads and staff of the internal audit department. Participants completed a survey and an interview as methods for data collection and analysis. Results suggest that the Internal Auditor provides support and advice for the company. The auditor complies with the regulations of the department. The auditor also monitors the operations of the company to enforce the institutional objectives. Keywords: Internal Auditing, Financial and administrative operations, Incidence, Coac Kullki Wasi Ltda. Reviewed by: MsC. Adriana Cundar Ruano, Ph.D. ENGLISH PROFESSOR c.c. 170926868534